Shopping and Crime - Bamfield, J. author. aut Link
IX, 325 p.
Keywords: An interdisciplinary study of retail crime as a cultural phenomenon, drawing on economics, criminology and management to present a comprehensive explanation for the growth in retail thefts. This topical study explores crime prevention as a management issue, using criminomics, a concept based on commercial realities rather than maximising arrests.